FACTORS EXTERNAL AND INTERNAL INDIVIDUAL ENCOURAGING THE DECISION TO SHOP AT FACTORY OUTLET - Sembiring, Rosmaniar (Dinasti International Journal of Management Science, 2020)
Factory Outlet is one type of industry that sells a wide variety of household purposes, at first the concept, Factory Outlet (FO) is a store that sells clothing-apparel export quality factory price/cost, and if you want to survive in the service industry should have orientation on customer satisfaction. Along with the increase in world oil prices have a direct impact on rising prices of basic commodities, it is at the beginning enough to affect a decrease in the purchasing power, but gradually Factory Outlet back in the rush by buyers, it is not separated by the image FO selling cheap goods and export quality. The nature of Indonesian society which includes consumer is increasingly becoming attractive when getting bids from these outlets, ranging from a discount program or facilities offered. This makes the writer feel interested in doing research, because as far as this writer has not found similar research. Specifically, this study is based on external factors and internal individual people and their influence on the decision to shop devoted to consumers who have been shopping at the Factory Outlet. From the results of calculation Simple Linear Regression 1, X1 to Y, the obtained determination coefficient of 0.188 or equal to 18.8%, the figures actually mean the influence of external factors on the decision-making is 18.8%, 81.2% of other factors (100 % - 18.8%) can be explained by other factors. From the results of calculation Simple Linear Regression 2, X2 to Y, the obtained determination coefficient of 0.079 or equal to 7.9%, the figures actually mean the influence of internal factors on decision making was 7.9%, the other factor of 92.1% (100 % - 7.9%) can be explained by other factors. Regression results of the calculation, X1 along X2 to Y, the obtained Effect of external variables to the variable decision of 0487 or 48.7%. Internal variable to variable influence decision-making by 0073, or 7.3%. The influence of external variables and internal variables together to the variable decision of 0191 or 19.1%. The influence of other variables outside of this path analysis model for 0809, or 80.9%.